Sustainable Development of the Moravian Countryside - Vaishar, Antonín; Zapletalová, Jana (Journal for Geography, 2010)
This paper deals with problems of the contemporary Moravian countryside. It discusses the definition and perceptions of the countryside, its functions, current development trend, general characteristics and differentiation. Multifunctional development of the countryside is stressed. Problems of peripheral countryside are considered to be the most serious, and small towns in these areas play an extremely important role. The sustainability of some communes with less than 200 inhabitants seems to be endangered most. The future importance of the countryside is seen in it being an alternative to the urban way of life, in the maintenance and cultivation of the landscape and in preserving local and regional traditions in the era of globalization. The human factor is of great importance. Main research sights are indicated.